Development of Katuk Leaf Dietary Supplement for Stunting Prevention Using an In Silico Method - Wafiq Azizah; Arwansyah Arwansyah; Sri M. Sabang; Sitti Nuryanti; Sitti Rahmawati (Jurnal Akademika Kimia, 2026)
Stunting is a chronic nutritional problem caused by long-term malnutrition, resulting in growth disorders in children. This study aims to predict the mechanism of action of secondary metabolites of katuk leaves as an alternative treatment for growth disorders in children (stunting). This research used network pharmacology to predict compounds from katuk leaves (Sauropus androgynus) based on literature studies. Network pharmacology analysis of katuk leaf (Sauropus androgynus) compounds identified 19 proteins, with HSP90AA1 having the highest degree, 14. This study uses molecular docking to predict interactions between active compounds, such as butyrolactone, phenol, and 2,3,4-trimethylpyrrole, and NAD-dependent protein deacetylase sirtuin-1, Aldo-keto reductase family 1 member C3, Carbonic anhydrase 5A, mitochondrial, Cyclin-dependent-like kinase 5, and Glucocorticoid receptor. The molecular docking results show that the butyrolactone compound has the highest binding affinity for 3 proteins, including NAD-dependent protein deacetylase sirtuin-1, with a binding affinity of -4.7 kcal/mol. The phenol compound has 3 proteins with the highest binding affinity, including Aldo-keto reductase family 1 member C3 at -5.5 kcal/mol. And the compound 2,3,4-trimethylpyrrole has 3 proteins with the highest binding affinity values, including the Glucocorticoid receptor, with a value of -5.8 kJ/mol.